Pemberdayaan Pemuda Karang Taruna Desa Widarapayung Wetan Kabupaten Cilacap melalui Pelatihan Membatik - Rosita Dwityaningsih; Taufan Ratri Harjanto; Saipul Bahri; Mardiyana Mardiyana; Ulikaryani Ulikaryani (Madani : Indonesian Journal of Civil Society, 2022)
Indonesia is the owner of an inscription certificate from UNESCO regarding the recognition of “The Representative List of The Intangible Culture Heritage of Humanity” for batik. This has an impact on increasing batik production due to increasing demand both from within the country and from abroad. However, there are problems in fulfilling the demand for batik. One of the problems is a decrease of skilled workers in batik especially for “batik tulis”. One that is experiencing a shortage of skilled workers is batik production in Cilacap Regency. Therefore, we empower the youth of the Widarapayung Wetan Village youth community by providing batik training. The purpose of this activity is to increase the interest of young people to pursue batik skills as well as to fulfil batik skilled workers. The results of a survey conducted at the end of the community service activity 80% of respondents agreed and 20% strongly agreed to explore batik skills.